The association of carotid intima-media thickness with serum Level of perfluorinated chemicals and endothelium-platelet microparticles in adolescents and young adults. (September 2016) - Lin, Chien-Yu; Chen, Pau-Chung; Lo, Shyh-Chyi; Torng, Pao-Ling; Sung, Fung-Chang; Su, Ta-Chen
Abstract: Perfluorinated chemicals (PFCs) have been widely used in a variety of products worldwide. Our previous study has documented a close association of higher serum level of perfluorooctane sulfonate (PFOS) with an increased carotid intima-media thickness (CIMT) in a cohort of adolescents and young adults. Herein, we further investigated the association of oxidative stress, circulating endothelial microparticles (EMPs) and platelet microparticles (PMPs) with PFCs and CIMT in humans. We recruited 848 subjects (12–30 years old) from a population-based sample to determine the relationship between serum levels of PFCs, EMPs (CD62E and CD31 +/CD42a −), PMPs (CD62P and CD31 +/CD42a +), and the urine levels of 8-hydroxydeoxyguanosine (8-OHdG) and CIMT. The results showed that CD31 +/CD42a − (endothelial apoptosis marker) and CD31 +/CD42a + (platelet apoptosis marker) increased significantly across quartiles of PFOS in multiple linear regression analysis. Furthermore, the elevation of CD31 +/CD42a − and CD31 +/CD42a + corresponded to the increase of the odds ratios of thicker CIMT (greater than 50th percentile) with higher serum PFOS concentration (greater than 50%) (OR = 2.86, 95% C.I. = 1.69–4.84, P  < 0.001) in logistic regression models. There was no association between PFC concentration and 8-OHdG. In conclusion, we found the positive association between PFOS and CIMT that was more evident when serum levels of EMPs (CD31 +/CD42a −) and PMPs (CD31 +/CD42a +) were elevated. Further studies are warranted to investigate the causal inference of PFOS exposure on endothelial cell damage and atherosclerosis. Highlights: The association between CIMT, serum PFCs and microparticles was studied among 848 persons in a young Taiwanese cohort. The serum PFOS concentration was positively associated with serum CD31 +/CD42a − and CD31 +/CD42a +. The positive association between PFOS and CIMT was more evident when CD31 +/CD42a − and CD31 +/CD42a + were elevated.